Exploring Financial Management Practices Used by Non-Governmental Organizations in Binga District in Zimbabwe - Mungombe, Argument; Dlamini, Banele; Moyo, Givemore (EuroEconomica, 2025)
Objectives This study explores the financial management practices employed by Non-Governmental Organizations (NGOs) in Binga District, Zimbabwe, with the aim of assessing their effectiveness and identifying areas for improvement. Prior Work Most available studies focused on urban areas or large international NGOs, leaving a gap in the understanding of financial management dynamics within smaller, community-based NGOs in rural regions like Binga. Approach Utilising a mixed-methods approach, quantitative data were gathered through a structured questionnaire administered to 57 respondents, alongside qualitative insights from interviews with key stakeholders. Quantitative data was analysed using SPSS version 22, and qualitative data was thematically analysed. Results The findings reveal a strong external reporting culture, exemplified by timely and consistent financial reporting to donors, as well as effective budget approval processes. However, significant challenges persist in areas such as segregation of duties, clarity of financial policies, and internal transparency, particularly in the sharing of audited financial statements with staff. Implications These insights underscore the need for NGOs to enhance their internal financial controls and communication strategies to foster accountability and improve operational efficiency. The study contributes to the existing literature on financial management in NGOs and offers practical recommendations for strengthening financial practices in the sector. Value This study provides valuable insights into the financial management practices of NGOs in Binga District, Zimbabwe, highlighting strengths in external reporting while identifying critical areas for improvement in internal controls and transparency, ultimately contributing to enhanced accountability and operational efficiency in the sector.